2021
DOI: 10.21037/atm-21-2417
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PAIP1 promotes the gallbladder tumorigenesis through regulating PLK1 level

Abstract: Background: Increasing evidence suggests that elevated expression of polyA-binding protein-interacting protein 1 (PAIP1) is associated with cancer development and progression. However, how PAIP1 promotes gallbladder cancer (GBC) is still unclear.Methods: Two GBC tissue-derived cell lines, NOZ and GBC-SD cells, were used in this study. Assays of cell proliferation, colony formation, apoptosis, and xenograft tumor model were performed to examine the tumorigenic effects of PAIP1. Immunohistochemical (IHC) stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Previous studies reported that PAIP1 knockdown inhibit the cell viability in a variety of cancer cell lines ( Bi et al, 2021 ; Guan et al, 2019 ; Li et al, 2019 ; Piao et al, 2018 ; Wang et al, 2019b ; Wang et al, 2019c ; Xie et al, 2020 ). Our study showed that PAIP1 knockdown can inhibit cell viability of liver cancer, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported that PAIP1 knockdown inhibit the cell viability in a variety of cancer cell lines ( Bi et al, 2021 ; Guan et al, 2019 ; Li et al, 2019 ; Piao et al, 2018 ; Wang et al, 2019b ; Wang et al, 2019c ; Xie et al, 2020 ). Our study showed that PAIP1 knockdown can inhibit cell viability of liver cancer, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…PAIP1 is a RNA binding protein, by which PAIP1 participates in regulation of translation ( Craig et al, 1998 ; Ivanov et al, 2019 ; Martineau et al, 2008 ; Martineau et al, 2014 ) and mRNA decay ( Grosset et al, 2000 ). PAIP1 are highly expressed in many types of cancer ( Bi et al, 2021 ; Guan et al, 2019 ; Li et al, 2019 ; Piao et al, 2018 ; Wang et al, 2019b ; Wang et al, 2019c ; Xie et al, 2020 ), inducing liver cancer ( Kim et al, 2020 ). However, the genome-widely regulated targets and mechanism of PAIP1 in liver cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations